Evaluation of Total Phenolics and Antibacterial Activity of Flavedo, Albedo, and Inner Membrane of Pamelo Peel (Citrus maxima (Burm.) Merr.) - Prasetyo, Angga; Findi Citra Kusumasari; Irene Ratri Andia Sasmita; Emi Kurniawati; Mohammad Mardiyanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pamelo peel (C. maxima (Burm.) Merr.) is a promising agricultural by-product that contains bioactive phenolic compounds. This study evaluated the total phenolic content and antibacterial activity of 70% ethanol extracts from three peel parts: flavedo, albedo, and inner membrane. Total phenolic content was quantified using the Folin-Ciocalteu method and antibacterial activity against Staphylococcus aureus was tested by the disc diffusion method. The results revealed significant variation in phenolic levels among the peel parts. Albedo contained the highest total phenolics, followed by the inner membrane and flavedo. Antibacterial testing showed that only the albedo extract exhibited inhibitory activity, whereas the other parts showed no activity. These results suggest that albedo is the most promising section of pomelo peel as a phenolic-rich part and an antibacterial agent. Further investigations are required to characterize the dominant phenolic compound and test antibacterial effects using purified fractions. Overall, this study highlights the potential of pamelo peel, particularly the albedo, as a value-added material for developing natural phenolic-based products.